Faktor Determinan Pembentuk Struktur Modal Pada Sektor Perbankan Konvensional Di Indonesia Periode 2015 -2019 - Farhan Fani Ihsan; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to determine the factors that influence the capital structure of conventional Indonesian banking in the 2015-2019 period. The variables used to measure the capital structure in this study are the current ratio (CR) that represents liquidity, Return on Asset (ROA) which represents profitability, the natural logarithm of total assets that represent bank size and total sales that represent growth. While for the dependent variable capital structure, measured using Debt to Equity Ratio (DER). There are 39 conventional banks listed on the Indonesia Stock Exchange which are used as the population in this study, then using purposive sampling techniques found 10 conventional banks that meet the criteria and serve as a research sample. This study using multiple linier regression analysis using time series data or based on time series. Where in the study the results obtained that the variable liquidity does not affect the capital structure. Then profitability has a significant positive effect on capital structure. And the growth variable is known that has no influence on the variable capital structure. Based on the simultaneous test, the results show that liquidity, profitability, bank size and growth variables have a significant positive effect on capital structure. Keywords: Conventional  Banking,  Capital  Structure,  Liquidity,   Profitability,                     Bank Size, Growth.